Arbitration and the constitution / Peter B. Rutledge. - Rutledge, Peter B. (Cambridge University Press, 2013)
Arbitration has become an increasingly important mechanism for dispute resolution, both in the domestic and international setting. Despite its importance as a form of state-sanctioned dispute resolution, it has largely remained outside the spotlight of constitutional law. This landmark work represents one of the first attempts to synthesize the fields of arbitration law and constitutional law. Drawing on the author's extensive experience as a scholar in arbitration law who has lectured and studied around the world, the book offers unique insights into how arbitration law implicates issues such as separation of powers, federalism and individual liberties.